Sundial in Traditional Architecture: Shrine of Imam Ali in Najaf Al-Ashraf as "Case Study" - Janjun, Mahmood; Mubarak, Neda; Al-Shlah, Rawaa (Journal of Engineering and Sustainable Development, 2026)
Building the shrines of Muslim imams in Iraq has a profound spiritual impact on the souls of its pioneers. Therefore, the designer was interested in creating an atmosphere that matches the spiritual and worship situation and linking it to a sustainable astronomical design in the architecture of the shrine of Imam Ali (peace be upon him). This was mentioned vaguely. Therefore, the research problem emerged about the relationship between the design of traditional sundials symbolically and sustainably. The goal is to reveal the relationship of the architectural design of the shrine’s architecture to the cosmic phenomenon represented by sundials. The current study adopts the analytical approach through two axes. Theoretical section: Collecting data related to sundials. In the practical study, five sundials in the shrine’s architecture were examined practically and in accordance with astronomical laws, and photographs were taken that confirmed the operation of the sundials in a sustainable manner annually.